2023
DOI: 10.1136/tsaco-2022-001038
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the implementation of a trauma center-based program to support primary care providers in managing opioids and pain after trauma hospitalization

Abstract: BackgroundDecreasing exposure to prescription opioids is critical to lowering risk of opioid misuse, overdose and opioid use disorder. This study reports a secondary analysis of a randomized controlled trial implementing an opioid taper support program directed to primary care providers (PCPs) of patients discharged from a level I trauma center to their homes distant from the center, and shares lessons for trauma centers in supporting these patients.MethodsThis longitudinal descriptive mixed-methods study uses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Many PCPs were preoccupied with COVID-19 care at the time of the study. Nevertheless, PCPs responding to a post-intervention survey reported that the program was acceptable, appropriate, and feasible [23]. The study's limited contact with PCPs attenuated the strength of the intended intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Many PCPs were preoccupied with COVID-19 care at the time of the study. Nevertheless, PCPs responding to a post-intervention survey reported that the program was acceptable, appropriate, and feasible [23]. The study's limited contact with PCPs attenuated the strength of the intended intervention.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, Braaf and colleagues identified variations in the quality of follow-up care provided by GPs, communication barriers, and discrepancies between patient expectations and GP assessments of need 23. Also, several studies have demonstrated difficulties in meeting patient needs for information during the transfer from specialty to primary care9 23 73 74 as well as communication barriers between specialists and GPs 75 76…”
Section: Discussionmentioning
confidence: 99%